Implementasi Pendidikan Kewarganegaraan dalam Menumbuhkan Kesadaran Demokrasi pada Mahasiswa - Helmi Suryana Siregar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of Civic Education (Pendidikan Kewarganegaraan/PKn) in fostering democratic awareness among university students. The research is grounded in the importance of Civic Education as a strategic medium for shaping democratic, critical, and participatory citizens. The study employed a quantitative approach with a pretest-posttest design, using simulated data of students’ average scores on democratic awareness before and after Civic Education learning. The results indicate a significant improvement across all aspects of democratic awareness, with an average increase of 1.14 points. The highest improvement was observed in classroom participation and critical thinking about political issues, while student involvement in organizations remained relatively low despite a positive increase. These findings highlight that Civic Education not only serves as a theoretical subject but also makes a tangible contribution to shaping students’ democratic, tolerant, and participatory character.